Real Time Bus Monitoring and Students Information System - Luke, CS; Gopal, R; Babu, M; Varghese, R; Sambasivan, D (International Journal of Computer Sciences and Engineering, 2025)
This paper proposes a real time college bus tracking and a student information system which runs on an android smart phone. The main purpose of this application is to provide exact location of a student’s respective bus in the Google maps. This application is very useful for parents. GPS tracking device receives signals from the GPS satellites. Depending on the time which the signal takes to reach the device from each satellite, the GPS receiver can calculate its exact location on the ground. The GPS tracking device can then route that information back to an online tracking system for mapping. We have also proposed a student information system for parents to view student’s details on android smart phone that keeps them updated about the latest events in the college or school. Parents can locate the bus in the route map. Using this application, parents can also get their ward’s mark details, attendance, performance rate, and can communicate with the teachers through chat.